2022
DOI: 10.1097/md.0000000000029578
|View full text |Cite
|
Sign up to set email alerts
|

Causes of death in primary plasma cell leukemia differ from multiple myeloma: A STROBE-compliant descriptive study based on SEER database

Abstract: The primary plasma cell leukemia (pPCL) is a rare but aggressive variant of multiple myeloma (MM). Few studies have focused on the differences in the causes of death between pPCL and MM. This study aimed to compare and evaluate the causes of death of patients with pPCL and MM. The data were collected from the Surveillance Epidemiology, and End Results (SEER) database. The demographic characteristics, survival, and causes of death in pPCL and MM patients were evaluated and compared. The competing risk regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…6,10 This is supported by a recent study using the Surveillance Epidemiology and End Results (SEER) database, which demonstrated that PCL had a higher mortality rate within 6 months compared to MM, lower median OS, and in contrast to MM, neither age at diagnosis nor race was associated with prognosis in PCL. 11 It has been increasingly clear that PCL has distinct biology from MM. For example, there are cytogenetic differences in PCL compared with MM, such as a higher prevalence of 17p deletions, hypodiploidy, and translocation t(14;16), as well as clinical ment.…”
Section: Discussionmentioning
confidence: 99%
“…6,10 This is supported by a recent study using the Surveillance Epidemiology and End Results (SEER) database, which demonstrated that PCL had a higher mortality rate within 6 months compared to MM, lower median OS, and in contrast to MM, neither age at diagnosis nor race was associated with prognosis in PCL. 11 It has been increasingly clear that PCL has distinct biology from MM. For example, there are cytogenetic differences in PCL compared with MM, such as a higher prevalence of 17p deletions, hypodiploidy, and translocation t(14;16), as well as clinical ment.…”
Section: Discussionmentioning
confidence: 99%